2018
DOI: 10.2141/jpsa.0170019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of <i>Saccharomyces Cerevisiae</i> Yeast Cell Walls to Diets with Mycotoxins on the Performance and Immune Responses of Broilers

Abstract: This study was conducted to evaluate the effect of Saccharomyces cerevisiae yeast cell walls (YCWs) in diets with low doses of aflatoxin B1 (AFB1) and ochratoxin A (OTA), alone or in combination, on broiler performance and immune response. A total of 210 male broilers aged 1-21 days were used. Broilers were completely randomized into seven treatments with five replicates of six broilers each, as follows: 1) control diet; 2) control + 350 μg/kg AFB1; 3) Control + 350 μg/kg OTA; 4) Control + 350 μg/kg AFB1 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
3
21
2
Order By: Relevance
“…Thus, the histological changes might not have been sufficient to cause significant reductions in the relative weights of the immune organs. In general, the suppression of lymphoid organ growth induced by AFB 1 is related to reduced numbers of lymphocytes [72,73,74]. It has been reported [73,75] that the reduction in the relative weight of the bursa induced by AFB 1 can be attributed to the decreased diameter of the lymphoid follicles and the reduced number of lymphocytes.…”
Section: Effects Of Aflatoxin B1 Produced By Aspergillus Flavus Anmentioning
confidence: 99%
“…Thus, the histological changes might not have been sufficient to cause significant reductions in the relative weights of the immune organs. In general, the suppression of lymphoid organ growth induced by AFB 1 is related to reduced numbers of lymphocytes [72,73,74]. It has been reported [73,75] that the reduction in the relative weight of the bursa induced by AFB 1 can be attributed to the decreased diameter of the lymphoid follicles and the reduced number of lymphocytes.…”
Section: Effects Of Aflatoxin B1 Produced By Aspergillus Flavus Anmentioning
confidence: 99%
“…For this reason, the dietary content of micronutrients have to be increased by an average of 20% [ 18 , 19 ]. Besides, clay adsorbents could be used in yeast cell walls ( Saccharomyces cerevisiae ) [ 20 , 21 , 22 ]. However, the effectiveness of mycotoxin absorbents themselves ranges from 20% to 80%.…”
Section: Introductionmentioning
confidence: 99%
“…In aquaculture, for example, their role in reducing sea-louse parasitism to improving immunity has been investigated [18,20] In dogs, the inclusion of YCW helped improve gut health and generated positive immunomodulatory effects [31]. A study on broilers showed improved intestinal immunoglobulin A and immune responses in feeds with YCW inclusion [32]. These studies emphasize the significance and relevance of the assessments presented in this study.…”
Section: Discussionmentioning
confidence: 72%